The Effect of Work Discipline and Work Environment on Employee Performance Sustainability Mediated by Job Satisfaction in Insurance Companies in South Jakarta - Ikkiu, Melia; Yuliantini, Tine (Journal Research of Social Science, Economics, and Management, 2026)
This study examines the influence of work discipline, work environment, and job satisfaction as mediating variables on sustainable employee performance at an insurance company in South Jakarta. Data on employee work effectiveness indicates a fluctuating number of underwork hours. This phenomenon was evident in August 2022, reaching 14 hours (loss hours), or approximately 20% of the total working hours. This trend continued in the following months, which were considered to have relatively high numbers of lost hours. Furthermore, the researchers conducted a pre-survey on work performance, work discipline, work environment, and job satisfaction among 30 employees. This study aims to measure and analyze the influence of work discipline, work environment, and job satisfaction on sustainable employee performance as mediating variables. This research employed a quantitative approach. The population consisted of 300 permanent employees, with a sample of 166 respondents determined using the Slovin formula and purposive sampling technique. Data were collected through structured questionnaires and analyzed using the Structural Equation Modeling (SEM) method with the assistance of Smart PLS software. The results show that work discipline and work environment have a positive and significant effect on job satisfaction and sustainable employee performance. Furthermore, job satisfaction also has a positive and significant effect on sustainable employee performance. Mediation analysis reveals that job satisfaction plays a partial mediating role in the relationship between work discipline and work environment on sustainable employee performance.